ANALISIS ANOMALI SINYAL ULTRA LOW FREQUENCY (ULF) GEOMAGNET SEBELUM TERJADI GEMPA 29 SEPTEMBER 2004 DI BIAK - Fitri Nuraeni (Pusbindiklat - LIPI, 2009)
Ultra Low Frequency (ULF) anomalies on geomagnetic variation data can be caused by external disturbances such as from the sun or space and internal disturbances from the earth. Before the 5.4 Richter Scale earthquake at Biak on September 29, 2004, there are anomalies that might be caused by electromagnetic emission from the earth's inner layer. These anomalies have been detected on geomagnetic signal in ULF band (10 — 600 sec periods). This paper will discuss the anomaly that was detected before the earthquake, and whether it was a local event within the earth's inner layer that happened because of the earthquake's preparation phase or was it actually caused by external disturbances. Data that is being used is the H and Z component of geomagnetic data variation. The Fast Fourier Transform method (FFT method) is being used to process the geomagnetic signal so the data can be filtered by bandpass filter. The Z/H polarization method is being used to analyze the result. Dst and Kp indices are also used to determine whether the anomaly is caused by external or internal disturbances.